Electron-microscopy of intact nuclear DNA from human cells. - McCready, S; Akrigg, A; Cook, P (1979)
Structures retaining many of the morphological features of nuclei may be released by lysing human cells in a non-ionic detergent and 2 M NaCl. Such nucleoids contain all the nuclear DNA packaged within a flexible cage of RNA and protein. HeLa nucleoids have been spread at an air-water interface and viewed in the electron microscope. A tangled network of superhelical fibres surrounds the collapsed cage. Irradiation with gamma-rays abolishes supercoiling and treatment with the untwisting enzyme or a low concentration of ethidium reduces it. A high concentration of ethidium induces supertwisting. The nuclear DNA of higher cells can be isolated naked, supercoiled and intact.